DBMS : tools and strategies for IS professionals (Miller Freeman Publ., 1988)
Continues in part: Business software.Merger of: Database programming & design, ISSN 0895-4518;Intelligent enterprise (San Mateo, Calif.), ISSN 1524-3621.